Studies on in vitro antioxidant and antistaphylococcal activities of some important medicinal plants - Mishra, A.; Kumar, S.; Bhargava, A.; Sharma, B.; Pandey, A. K. (Cellular and Molecular Biology, 2011)
Oxidative stress is initiated by free radicals, which seek stability through electron pairing with biological macromolecules in healthy human cells and cause protein and DNA damage along with lipid peroxidation. Many phytochemicals have been found to play as potential antioxidants and antimicrobials. In the present study antioxidant and antistaphylococcal activities of Bauhinia variegata, Tinospora cardifolia and Piper longum have been determined. Total phenolic contents in plant extracts were estimated and different amounts of phenolic contents were found in B. variegata, T. cardifolia and P. longum extracts. The antioxidant activity of the extracts was compared with standard antioxidants such as, BHA, BHT, quercetin, ascorbic acid and propyl gallate. The % scavenging activity gradually increased with increasing concentrations of the test extracts in DPPH radical scavenging assay. Dose dependent antioxidant activity pattern was also observed in phosphomolybdate assay. Antioxidant activity was directly correlated with the amount of total phenolic contents in the extracts. As compared to B. variegata, the extracts from other two plants exhibited higher antioxidant activity. In disc diffusion assays several solvent extracts derived from test plants inhibited the growth of Staphylococcus aureus. Maximum inhibitory efficacy was observed in T. cardifolia extracts. However, the lowest minimum bactericidal concentration (MBC) (0.43 mg/ml) was recorded for ethyl acetate and acetone extracts of P. longum. This study demonstrates notable antioxidant and anti-staphylococcal roles assigned to some plant extracts tested.